(untitled) (Journal of the College of Basic Education, 2024)
The objective of the current research is to identify the self-regulation skills of kindergarten teachers, and the researcher relied on the analytical descriptive approach and on the self-regulation skills scale. 79), and by the Wackeronbach internal consistency method (0.85(When processing the study data statistically using the Pearson correlation coefficient, the t-test for two independent samples, the Vachronbach equation, the t-test equation for one value, the results revealed that the research sample had self-regulation skills, and recommended the need to intensify training courses for Riyadh teachers, especially for teachers with limited experience in The field of kindergarten, and the preparation of training programs on the research variables for female students in the kindergarten department commensurate with their future work. years of service, educational attainment.